Steroids and insulin resistance in pregnancy - Vejrazkova, Daniela; Vcelak, Josef; Vankova, Marketa; Lukasova, Petra; Bradnova, Olga; Halkova, Tereza; Kancheva, Radmila; Bendlova, Bela (The Journal of steroid biochemistry and molecular biology, 2014)
Metabolism of glucose during pregnancy reflects the equilibrium between lactogenic hormones stimulating insulin production and counterregulatory hormones inducing insulin resistance. In physiological pregnancies, insulin-mediated glucose uptake is substantially decreased and insulin secretion increased to maintain euglycemia. This common state of peripheral insulin resistance arises also due to steroid spectra changes. In this review article, we have focused on the role of steroid hormones (androgens, estrogens, gestagens, mineralocorticoids, glucocorticoids, as well as secosteroid vitamin D) in the impairment of glucose tolerance in pregnancy and in the pathogenesis of gestational diabetes mellitus. This article is part of a Special Issue entitled 'Pregnancy and Steroids'.
Keywords: těhotenství; Insulin Resistance; Gonadal Steroid Hormones; lidé; Adrenal Cortex Hormones; Insulin resistance; Vitamin D; pohlavní steroidní hormony; Female; Sex Hormone-Binding Globulin; vitamin D; Gestational diabetes mellitus; gestační diabetes; Humans; globulin vázající pohlavní hormony; inzulinová rezistence; Steroids; hormony kůry nadledvin; Glycoregulation; zvířata; Pregnancy; ženské pohlaví; Animals; Diabetes, Gestational